Nutraceuticals and Human Health - Scotto D'Abusco, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this Special Issue, we have published papers on the health-promoting effects of nutraceuticals from different sources, and their effects in different pathologies. Extracts from plants have been analyzed, for example, extracts from olive leaves, Mikania micrantha, the devil's claw, raspberries and others, alongside marine phytoplankton, egg-yolk and marketed dietary supplements. The effects of these extracts and dietary supplements have been studied in diseases associated with obesity, and in diseases where inflammation pathways are involved. The effectiveness of resveratrol and curcumin to support the anticancer activity of cisplatin has also been reported, as well as the ability of devil's claw root extract to stimulate the CB2 receptors in synoviocytes in osteoarthritis patients. The anti-oxidant effect of marine phytoplankton has been studied on muscle damage, both in humans and in an animal model, and the effects of the metabolite of antocianin were analyzed in a mouse model of amyotrophic lateral sclerosis. Finally, reviews on the use of lactoferrin, ω3 and ω6 and abscisic acid have been reported, in addition to the crosstalk between prostate cancer and microbiota inflammation. Although it is not yet possible to draw definitive conclusions on the use of nutraceuticals, several mechanisms of action for many of them have been further clarified.